Exploring the relationship between assessed dispositions and assessed student teaching success of teacher education candidates from an NCATE accredited teacher preparation program - Bland, Lendi L. (Kansas State University, 2014)
Research regarding dispositions dates back seven decades; but because of challenges in measuring, identifying and monitoring dispositions, teacher education programs have only recently developed procedures to document and assess candidates’ dispositions (Albee, & Piveral, 2003). The question remains, are teacher educators prepared for this challenge? Dispositions can be difficult to identify and measure and teacher educators are not necessarily trained in the development of assessments. By using data gathered at an NCATE accredited teacher education institution, the researcher hoped to examine one institution’s approach to assessing dispositions as part of an overall system to assess successful teaching. The purpose of this study was to determine if there was a relationship between the results of disposition assessments completed by university supervisors at the end of Block 2 and the results of final student teacher assessments completed by university supervisors at the end of Block 3. Scores from the Block 2 Coordinator’s Evaluation of Intern form and the final University Supervisor Assessment of Student Teacher/Intern form were collected and correlated using the Spearman’s Rho. The resulting scores were analyzed to determine if there was a statistically significant relationship. It was concluded that there was no significant relationship between the Block 2 Coordinator’s Evaluation of Intern form score and the final University Supervisor Assessment of Student Teacher/Intern form score. This study underscores the difficulty of assessing dispositions, and shows that teacher education programs need to establish reliability and validity on forms used to assess candidates’ dispositions.
Keywords: Dispositions; Undergraduate teacher education; Elementary Education (0524)